Updating The General Practitioner on The Association Between Teeth Loss and Temporomandibular Disorders: A Systematic Review - Leal, Marília da Cunha Feio; Castro, Micaele Maria Lopes; Sosthenes, Márcia Consentino Kronka (European Journal of Dentistry, 2022)
The belief about a possible association between the absence of one or more teeth and the presence of temporomandibular disorders (TMD), although old, is still present among the dental class. Although evidence points to a lack of association between loss of posterior support and the presence of TMD, we do not have critical studies on the extent, quantity, or location of these losses. In this sense, this systematic review aims to investigate the association between tooth loss and the presence of TMD signs or diagnostic subgroups. Search strategies using a combination of keywords tooth loss and TMDs were performed in six databases (PubMed, Embase, Web of Science, Livivo, Lilacs, and Scopus) and gray literature from August to September 2020. Observational studies that investigated the association between tooth loss in TMD were considered. The risk of bias was assessed using the Joanna Briggs Institute (JBI) Critical Assessment Checklist for cross-sectional analytical studies, case–control, and cohort studies. Finally, the level of certainty measured by the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) was assessed. Six articles were included in the review according to the eligibility criteria. Of these, five had a high risk of bias and one had a moderate risk. Only one study showed an association between the loss of posterior teeth and the presence of joint sounds and joint pain, the others found no significant association with sign or TMD subgroups diagnostic.There is no scientific evidence to support the association between one or more tooth loss and the presence of TMD signs and symptoms or diagnostic subgroups.
Keywords: tooth loss; dental occlusion; temporomandibular joint; systematic review